A new genus and species of cyproideid amphipod associated with unstalked crinoids on the Great Barrier Reef, Australia - Lowry, J. K.; Azman, B. A. R. (Zootaxa, 2008)
Gbroidea dingaalana, a new genus and species of cyproideid amphipod is described from Lizard Island, Great Barrier Reef, Australia. The species is associated with the unstalked crinoids, Comathus briareus, Comatula rotalaria and Zygometra microdiscus.